IL-10 Expression and Pulmonary Fibrosis in COVID-19 and Non-COVID-19: A Cross-sectional Study - yasmin, dzakiyah; Anang Marhana, Isnin; Sandhika, Willy (International Journal Labs, 2025)
Indonesia was declared the country with the highest number of COVID-19 cases in ASEAN, and East Java was the province with the highest confirmed case fatality rate (7.3%) in 2021. In the case of COVID-19, there was a drastic elevation of the anti-inflammatory cytokine IL-10. This study aimed to ensure the role of IL-10 against pulmonary fibrosis in COVID-19 and non-COVID-19 patients. This study is a cross-sectional (non-experimental) study. The study sample consisted of 40 lung tissue samples from COVID-19 and non-COVID-19 patients at Dr. Soetomo General Academic Hospital, Surabaya. The IL-10 antibody reagent (GTX632359, GeneTex) was used to assess IL-10 expression, and hematoxylin and eosin (H&E) were used to determine the degree of pulmonary fibrosis. For Spearman's correlation, the data were analyzed using Statistical Package for the Social Sciences (SPSS). The mean percentage of IL-10 expression in COVID-19 patients (40.07%) was higher than in non-COVID-19 patients (26.60%). However, the mean for the degree of pulmonary fibrosis score in non-COVID-19 patients (4.43) was higher than in COVID-19 patients (3.67). Furthermore, a negative correlation (p=0.000; r=-0.281) was found between the percentage of IL-10 expression and the degree of pulmonary fibrosis. The percentage of IL-10 expression in macrophage cells had a significant negative correlation with the degree of pulmonary fibrosis score.